2021
DOI: 10.14569/ijacsa.2021.0120176
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Biometric Fusion System of Fingerprint and Face using Whale Optimization

Abstract: In the field of wireless multimedia authentication unimodal biometric model is commonly used but it suffers from spoofing and limited accuracy. The present work proposes the fusion of features of face and fingerprint recognition system as an Improved Biometric Fusion System (IBFS) leads to improvement in performance. Integrating multiple biometric traits recognition performance is improved and thereby reducing fraudulent access.The paper introduces an IBFS comprising of authentication systems that are Improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…In Table 5, it is shown that the accuracy of the proposed method is better than Mwaura et al ( 2017), Somashekhar and Nijagunarya (2018) as well as Alazawi et al (2019). The result of the proposed method is slightly lower than Aleem et al (2020), Kumar et al (2021), andPawar et al (2021) because of the two samples: sample 7 and sample 18, as shown in Table 4. Overall, the result of the proposed method is comparable to Aleem et al (2020), Kumar et al (2021) and Pawar et al (2021).…”
Section: Methods Applied Accuracymentioning
confidence: 82%
See 4 more Smart Citations
“…In Table 5, it is shown that the accuracy of the proposed method is better than Mwaura et al ( 2017), Somashekhar and Nijagunarya (2018) as well as Alazawi et al (2019). The result of the proposed method is slightly lower than Aleem et al (2020), Kumar et al (2021), andPawar et al (2021) because of the two samples: sample 7 and sample 18, as shown in Table 4. Overall, the result of the proposed method is comparable to Aleem et al (2020), Kumar et al (2021) and Pawar et al (2021).…”
Section: Methods Applied Accuracymentioning
confidence: 82%
“…The result of the proposed method is slightly lower than Aleem et al (2020), Kumar et al (2021), andPawar et al (2021) because of the two samples: sample 7 and sample 18, as shown in Table 4. Overall, the result of the proposed method is comparable to Aleem et al (2020), Kumar et al (2021) and Pawar et al (2021). As mentioned in the previous section, match score level fusion contains the richest information for all input data, less noise, and is relatively easy to implement.…”
Section: Methods Applied Accuracymentioning
confidence: 91%
See 3 more Smart Citations